Blocking the information war? Testing the effectiveness of the EU's censorship of Russian state propaganda among the fringe communities of Western Europe - Christiern Santos Okholm; Amir Ebrahimi Fard; Marijn ten Thij (Internet Policy Review, 2024)
In response to Russia's full-scale invasion of Ukraine in February 2022, the European Union banned or geo-blocked Russian propaganda media fearing the effects of the Kremlin's information warfare on internal public opinion during the largest security crisis in modern history. We investigate the blocks' effectiveness in limiting the sharing of Russian propaganda media content among vulnerable Western European fringe communities. By studying posting patterns on Facebook three months before and after the geo-block, we find that the geo-block successfully reduced the sharing of Russian propaganda media content among fringe communities and did not increase the sharing of other non-banned pro-Russian media. Furthermore, we found the geo-block increased sharing of content from alternative platforms, while the share of pro-Russian content doubled among these posts. These findings show the effectiveness of censorship in limiting foreign influence campaigns on major platforms, but they also show how alternative platforms allow for the continued spread of banned content.
Keywords: 300; Censorship; Propaganda; Information war; Platforms; Russia